Comparative assessment of efficacy of artery ligation versus rubber band ligation for management of haemorrhoids in Southern Rajasthan - Agrawal, Mathura Prasad; Pateriya, Anurag; Samar, Surendra Kumar (International Surgery Journal, 2021)
Background: One of the commonest complaints presenting in the surgical out patient department (OPD) is haemorrhoids. Commonest types of haemorrhoids are grade II and III. There is a wide number of modalities that can be adopted for their management. It depends on the skill of the surgeon and preferences of the patient. The present study was designed to ascertain if two modalities of artery ligation and band ligation are comparatively equal or not in managing symptomatic grade II and III haemorrhoids in Rajasthan. Methods: The study comprised of 100 subjects who were randomly divided in two groups based on the procedure to be followed. The subjects were told about the study and its objective. Results: The observations reported that among the selected study population there were more relapses in band ligation as compared to artery ligation. Conclusions: This led to the conclusion that despite its painful and traumatic methodology, haemorrhoid artery ligation still provides a better outcome.